2011
DOI: 10.1007/s10327-011-0311-4
|View full text |Cite
|
Sign up to set email alerts
|

Bchex virulence gene of Botrytis cinerea: characterization and functional analysis

Abstract: We previously identified Bchex as a highly expressed gene during filamentous growth in Botrytis cinerea. The gene encodes the principal protein of the Woronin body and has been shown to seal septal pores in response to cellular damage. In the present study, Southern blot analysis of genomic DNA indicated that the gene exists as a single copy in the B. cinerea genome. The gene was differentially expressed during various developmental stages: expression was high in germinating conidia and the mycelial stage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…2 ). BcBMP1, BcPME1 , BcPLS1, BcXyn, BcPLC1 and Bchex were previously found to be involved in plant infection processes and defined as essential determinants for Bc pathogenicity (47, 5964). All virulence genes assayed exhibited statistically significant down-regulation upon CK treatment ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). BcBMP1, BcPME1 , BcPLS1, BcXyn, BcPLC1 and Bchex were previously found to be involved in plant infection processes and defined as essential determinants for Bc pathogenicity (47, 5964). All virulence genes assayed exhibited statistically significant down-regulation upon CK treatment ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the expression of bcaox 1, a gene related to oxidative stress in fungi, is increased in presence of polygodial, which suggest a mitochondrial dysfunction due to damage of ATP-forming complexes located in the inner membrane ( Figure 8 d). Finally, in Figure 8 c it is clearly seen that polygodial induces a strong underexpression of bchex , which is a gene involved in hyphal growth damage [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in the presence of polygodial the expression level of bchex is 4–5 times below the expression measured for the control, whereas in the presence of drimenol this gene is 20 times overexpressed. This gene encodes to the principal protein of the Woronin body whose main function is to seal septal pores in response to cellular damage, and in a previous work we have shown that growth of fungi mutation lacking this gene is greatly reduced [ 20 ]. Thus, these results confirm that polygodial is not affecting mycelial growth and, therefore, its effect may be completely attributed to inhibition of germination.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that other compounds than those measured in our study (glucose, fructose, sucrose) may be implicated, or that only some of the soluble sugars, such as fructose and sucrose, are implicated in the response to infection. The recent description of a mutant of B. cinerea incapable of using fructose as a sole carbon source (Aguayo et al 2011) should provide a useful tool to investigate this subject further. Competition for nutrients is a common mode of action of biocontrol agents on plant surfaces.…”
Section: Relationship Between Stem Tissue Content and The Severity Ofmentioning
confidence: 99%